“Someone Who Has Been in My Shoes”: The Effectiveness of a Peer Support Model for Providing Support to Partners, Family and Friends of Child Sexual Abuse Material Offenders - Jones, Christian (Victims & offenders, 2023)
Reports of child sexual abuse material (CSAM) on the internet are rapidly increasing and the number of people accessing it is substantial. Many of these men have partners or families who are impacted by their CSAM use. These families experience negative mental health and social outcomes as a result. Despite this, there are limited services that provide support to this population. In this article, we examine the findings of an evaluation of PartnerSPEAK, a service in Victoria, Australia, that supports the non-offending partners and families of CSAM offenders. The evaluation included a survey of 53 clients as well as seven in-depth interviews. The findings showed that the peer support model utilized by PartnerSPEAK offered effective support for this underserved client group including the reduction of shame and isolation.